Surfactant Protein A in Exhaled Endogenous Particles Is Decreased in Chronic Obstructive Pulmonary Disease (COPD) Patients: A Pilot Study. - Mona Lärstad; Ann-Charlotte Almstrand; Per Larsson; Björn Bake; Sven Larsson; Evert Ljungström; Ekaterina Mirgorodskaya; Anna-Carin Olin (PLoS ONE)
Background Exhaled, endogenous particles are formed from the epithelial lining fluid in small airways, where surfactant protein A (SP-A) plays an important role in pulmonary host defense. Based on the knowledge that chronic obstructive pulmonary disease (COPD) starts in the small airway epithelium, we hypothesized that chronic inflammation modulates peripheral exhaled particle SP-A and albumin levels. The main objective of this explorative study was to compare the SP-A and albumin contents in exhaled particles from patients with COPD and healthy subjects and to determine exhaled particle number concentrations. Methods Patients with stable COPD ranging from moderate to very severe (n = 13), and healthy non-smoking subjects (n = 12) were studied. Subjects performed repeated breath maneuvers allowing for airway closure and re-opening, and exhaled particles were optically counted and collected on a membrane using the novel PExA® instrument setup. Immunoassays were used to quantify SP-A and albumin. Results COPD patients exhibited significantly lower SP-A mass content of the exhaled particles (2.7 vs. 3.9 weight percent, p = 0.036) and lower particle number concentration (p<0.0001) than healthy subjects. Albumin mass contents were similar for both groups. Conclusions Decreased levels of SP-A may lead to impaired host defense functions of surfactant in the airways, contributing to increased susceptibility to COPD exacerbations. SP-A in exhaled particles from small airways may represent a promising non-invasive biomarker of disease in COPD patients.